Assessment of fetal-maternal haemorrhage in mothers with hereditary persistence of fetal haemoglobin. - Patton, W N (1990)
Kleihauer examination of peripheral blood cannot be used reliably to detect transplacental fetal-maternal haemorrhage in mothers with hereditary persistence of fetal haemoglobin (HPFH). In Rh(D) negative pregnancies diagnostic confusion with a large fetal-maternal haemorrhage could result in the administration of inappropriately excessive amounts of anti-D immunoglobulin, and the inability to diagnose and quantify transplacental haemorrhage in maternal HPFH by current methods could result in insufficient anti-D administration and subsequent Rh(D) sensitisation. Accordingly, a method to detect and quantify fetal-Rh(D) positive maternal haemorrhage using erythrocyte fluorescent immunocytometry was developed. An indirect immunofluorescence method with IgG anti-D immunoglobulin as the primary antibody was used, combined with quantitative analysis on a fluorescence activated cell sorter. The method was accurate, specific, and sensitive and could detect a contaminating population of 0.1% Rh(D) positive cells in Rh(D) negative blood--a level of fetal-maternal haemorrhage well covered by a single dose of 500 IU of anti-D immunoglobulin.